Connecting Yemen to Capital: Telegraph Network of Yemen Province and Connection Lines - Diren Çakılcı (Türkiyat Mecmuası)
Despite the fact that there are records which are dated to beginning of the 1870s about the construction of telegraph lines within the province of Yemen, it was not possible until the end of the 19th century to establish a connection between the centers of the province with one another, and also directly between provincial network and the capital. The first telegraph line expansion to the province was proposed in 1872 as a parallel landline road from Damascus to Medina, Jeddah, Kunfuda, and Hudaydah, but it was never completed. Efforts were made to establish a fast communication network to reach Payitaht [Capital] through international telegraph offices around such as Aden, Suakin, Musavva, Perim Island. Submarine cables of the Eastern Telegraph Company located in the Red Sea were of major importance for this issue. The distance from Yemento the Ottoman network, the natural obstacles of the geography, the permanent revolts in the region and the distresses in the state budget have prevented for many years the construction of the provincial lines. At the end of the 19th century, the demand for telegraph increased even more as a result of the activities of the foreigners in the region and the deepening rebellions. The development of Yemen Province telegraph lines, Ottoman State's attempts and solutions in this direction, as well as the communication traffic that existed along the Red Sea beaches, are all explored in this paper. This study purports to make a contribution is made for the narration of regions’ military, political, and economic history.